Removal of Chemical Nitrogen and Phosphorus of Micro-Polluted Water with Modified Zeolite Subsurface Wetland - Wang, Hao; Li, Xuejin (Asian Journal of Chemistry, 2013)
As the main matrix of subsurface wetland, the modified zeolite was applied to the treatment of micro-polluted water. The wetlands' removal effect on the main pollutant in micro-polluted water was measured when the intermittent influent was adopted and the hydraulic loading was controlled to 0.278 m3/(m2 d) and 0.139 m3/(m2 d) and 0.093 m3/(m2 d). The results showed that the modified zeolite's removal rate on ammonia nitrogen, total nitrogen and total phosphorus were 86.7, 91.4 and 86.9 %, respectively, which showed that the best operating hydraulic loading was 0.093 m3/(m2 d). Furthermore, the subsurface wetland manifested increased removal effect on the pollutant with the decrease of hydraulic load.